2023
DOI: 10.1080/19336918.2023.2258539
|View full text |Cite
|
Sign up to set email alerts
|

Overview of hepatocellular carcinoma: from molecular aspects to future therapeutic options

Sugan Panneerselvam,
Cornelia Wilson,
Prem Kumar
et al.

Abstract: Hepatocellular carcinoma (HCC) is the seventh most highly prevalent malignant tumor globally and the second most common cause of mortality. HCC develops with complex pathways that occur through multistage biological processes. Non-alcoholic fatty liver disease, metabolic-associated fatty liver disease, alcoholic liver disease, autoimmune hepatitis, hepatitis B, and hepatitis C are the causative etiologies of HCC. HCC develops as a result of epigenetic changes, protein-coding gene mutations, and altered signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 162 publications
0
3
0
Order By: Relevance
“…Depletion of p53-a tumor suppressor protein-favors the regression of the differentiation of mature hepatocytes into progenitor cells. The alteration in the formation of HCC, followed by a genetic mutation in the Wnt and Notch signaling pathways, acts mainly in the development of embryonic cells, coordinating cell differentiation, cell proliferation, and apoptosis [221].…”
Section: Mafld and The Development Of Hepatocellular Carcinomamentioning
confidence: 99%
“…Depletion of p53-a tumor suppressor protein-favors the regression of the differentiation of mature hepatocytes into progenitor cells. The alteration in the formation of HCC, followed by a genetic mutation in the Wnt and Notch signaling pathways, acts mainly in the development of embryonic cells, coordinating cell differentiation, cell proliferation, and apoptosis [221].…”
Section: Mafld and The Development Of Hepatocellular Carcinomamentioning
confidence: 99%
“…Gut microbiota dysbiosis, together with altered metabolite profiles and compromised gut barrier integrity, profoundly disrupts immune homeostasis in the liver and consequently fosters carcinogenesis. Clinical studies have revealed augmented numbers of regulatory T cells and diminished numbers of CD3+ and CD8+ T cells in the peripheral blood and tumor specimens of patients with HCC-findings correlated with poorer prognosis [117][118][119] . Modulation of the gut microbiota has potential to reinvigorate anti-tumor responses.…”
Section: Gut Microbiota Dysbiosis and Hccmentioning
confidence: 99%
“…HBV is the main etiological factor associated with HCC in India. But right now, India lacks access to thorough HCC data [3].…”
Section: Introductionmentioning
confidence: 99%